2018
DOI: 10.3390/molecules23082035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Anthocyanidin Glucosides on Lutein Uptake by Caco-2 Cells, and Their Combined Activities on Anti-Oxidation and Anti-Inflammation In Vitro and Ex Vivo

Abstract: The interactive effects on anti-oxidation and anti-inflammation of lutein combined with each of the six common anthocyanidin glucosides were studied in both chemical and cellular systems. The combined phytochemicals showed an antagonism in the inhibition of lipid oxidation in a liposomal membrane, but showed an additive effect on cellular antioxidant activity in Caco-2 cells. Lutein was an active lipoxygenase inhibitor at 2–12 μM while anthocyanins were inactive. The concentration of lutein when it was used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…None of the polyphenol samples displayed cytotoxic effects on the Caco-2 cells (data not shown). Similarly, previous studies reported that non-encapsulated and encapsulated polyphenolic samples at concentrations that exhibited CAA in Caco-2 cells did not demonstrate any cytotoxic effects [83,89,91,97].…”
Section: Cytotoxicitysupporting
confidence: 65%
See 1 more Smart Citation
“…None of the polyphenol samples displayed cytotoxic effects on the Caco-2 cells (data not shown). Similarly, previous studies reported that non-encapsulated and encapsulated polyphenolic samples at concentrations that exhibited CAA in Caco-2 cells did not demonstrate any cytotoxic effects [83,89,91,97].…”
Section: Cytotoxicitysupporting
confidence: 65%
“…The encapsulated 10 µM combinations had improved CAA from additive (non-encapsulated) to synergistic interactions for most samples, whereas for the 100 µM samples, majority additive interactions were observed (Table S3). Phan et al [91] and Phan et al [92] studied the 1:1 mole ratio combinations of the carotenoids lutein and β-carotene, respectively, with different anthocyanin glucosides and reported additive interactions towards CAA in Caco-2 cells. In another study, combinations of lycopene with anthocyanin glucosides had antagonistic interactions at a 1:1 mole ratio and additive interactions at a 3:1 mole ratio [93].…”
Section: Antioxidant Activity-dichlorofluorescein Diacetate (Dcfh-da)mentioning
confidence: 99%
“…In particular, malvidin-3-glucoside has been shown to have anti-inflammatory properties in a murine colitis model through the modulation of the integrity of the colon epithelium, gut microbiota, and gut metabolism [ 65 , 66 ]. Catechins and epicatechins influenced cellular response to oxidative stress and exerted intestinal anti-inflammatory properties by modulating several cell signaling pathways, such as NF-κB, mitogen-activated protein kinases (MAPKs), and transcription factor nuclear factor (erythroid-derived 2)-like 2 (Nrf2) [ 67 , 68 ]. Similarly, kaempferol counteracted gut inflammation by inhibiting the activation of the NF-κB signaling pathway in intestinal epithelial–endothelial co-culture model [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant and anti-inflammatory effects of LUT and its combination with six anthocyanidin glucosides were also evaluated chemically and in Caco-2 cells. LUT alone showed better results than the mixture with the other compounds, demonstrating antioxidant activity through inhibition of liposome peroxidation and anti-inflammatory effects via suppression of the in vitro lipoxygenase-1 activity and reduction in IL-8 and NO levels in Caco-2 cells [163].…”
Section: Lutein 421 In Vitro Studiesmentioning
confidence: 96%